Semantic effects on word naming in children with developmental dyslexia - Hennessey, Neville; Deadman, A.; Williams, Cori (Blackwell Publishing, 2010)
Repetition priming was used to examine whether children with dyslexia bias a lexical–semantic pathway when reading words aloud. For the dyslexic group (n=18, age 9.4–11.8 years), but not for age-matched controls (n=18, age 9.2–12.4 years), reaction times when naming pictures were faster after naming the corresponding word. A reading age-matched control group (n=24, age 6.8–8.9 years) showed similar priming effects to the children with dyslexia. The magnitude of repetition priming was greater for children with dyslexia with poor nonword reading and slower picture naming. Assuming repetition priming of picture naming is contingent on accessing lexical phonology via semantics, the results suggest less-skilled normal and disordered readers show a stronger bias towards a lexical–semantic pathway during word reading than skilled readers, and the severity of the phonological representations deficit modulates the strength of that bias in children with dyslexia.